2007
DOI: 10.1007/bf03324682
|View full text |Cite
|
Sign up to set email alerts
|

High baseline values of fat mass, independently of appendicular skeletal mass, predict 2- year onset of disability in elderly subjects at the high end of the functional spectrum

Abstract: High body fat and high BMI values were associated with a greater probability of developing functional limitations 2 years later in a population of elderly subjects at the high end of the functional spectrum. Moreover, in women, high baseline values of fat mass, independently of appendicular fat-free mass, were more likely to predict the future onset of functional limitations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 31 publications
2
28
2
Order By: Relevance
“…Data from other investigators suggest that the BMI cut‐point for increasing risk of disability may be lower than 35 kg·m −2 (22,29–31), particularly when outcomes involve tasks that require raising the centre of mass, e.g. ascending stairs (32). An interesting hypothesis is that the risk that added weight poses for physical disability may depend upon the demands of the task.…”
Section: Resultsmentioning
confidence: 99%
“…Data from other investigators suggest that the BMI cut‐point for increasing risk of disability may be lower than 35 kg·m −2 (22,29–31), particularly when outcomes involve tasks that require raising the centre of mass, e.g. ascending stairs (32). An interesting hypothesis is that the risk that added weight poses for physical disability may depend upon the demands of the task.…”
Section: Resultsmentioning
confidence: 99%
“…with 14.5%) and women (31.7% compared with 14.6%) than in nonobese counterparts (16), with every SD increment of BMI associated with a 5% reduction in the usual walking speed (17). Likewise, several longitudinal studies suggested a link between elevated BMI and gait-speed decline (18)(19)(20)(21). Although previous longitudinal data reported a direct association between the amount of fat mass (12) and an inverse (13) [or null (22,23)] association between the amount of muscle mass and development of self-reported incident mobility limitation, to the best of our knowledge, this is the first article to address the independent association between changes in measures of body composition and gait speed.…”
Section: Figurementioning
confidence: 94%
“…The odds risk of chair-rise debility increases nearly 6-fold in severely obese persons when compared with those who are not obese, and the ability to complete multiple chair rises diminishes with increasing adiposity. 43 Obesity is related to a loss in stair ascent ability over time, 44 and obesity increases difficulty of performing other tasks such as climbing a stool, cutting toenails, squatting, rising from a supine position from the floor, kneeling, rising from a squat, picking up coins from the floor, and 1-legged stance. 45 In obese Japanese women, pain modulates the difficulty of performing daily movements such as walking more than an hour, sitting on the floor with legs beneath, and climbing stairs.…”
Section: Functional Effects Of Musculoskeletal Painmentioning
confidence: 99%